Lumbar Ureteral Stenosis due to Endometriosis: Our Experience and Review of the Literature - Salvatore Butticè; Antonio Simone Laganà; Valeria Barresi; Antonino Inferrera; Giuseppe Mucciardi; Antonina Di Benedetto; Carmela Emanuela D'Amico; Carlo Magno (Case Reports in Urology)
Endometriosis is a chronic gynaecological disorder characterized by the presence of endometrial tissue outside the uterus. The disease most often affects the ovaries, uterine ligaments, fallopian tubes, and cervical-vaginal region. Urinary tract involvement is rare, accounting for around 1%-2% of all cases, of which 84% are in the bladder. We report a case of isolated lumbar ureteral stenosis due to endometriosis in a 37-year-old patient. The patient came to our observation complaining from lumbar back pain and presented with severe fever. The urological examination found monolateral left positive sign of Giordano. Blood tests evidenced marked lymphocytosis and increased valued of C-reactive protein. Urologic ultrasound showed hydronephrosis of first degree in the left kidney and absence of images related to stones bilaterally. Uro-CT scan evidenced ureteral stenosis at the transition between the iliac and pelvic tracts. We addressed the patient to surgery, and performed laparoscopic excision of the paraureteral bulk, endoscopic mechanical ureteral dilation, and stenting. The histological examination evidenced glandular structures lined by simple epithelium and surrounded by stroma. Immunohistochemical test of the glandular epithelium showed positivity for estrogen and progesterone receptors and moreover stromal cells were positive for CD10. The finding suggested a very rare diagnosis of isolated lumbar ureteral endometriosis.